2021
DOI: 10.2147/ndt.s333569
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Medicine for Patients with Cognitive Impairment: An Observational Study

Abstract: Purpose:The potential effects of herbal medicine for patients with cognitive disorders have been reported in various human and animal studies. This study aimed to explore the effect of herbal medicine treatment according to the Korean Medicine (KM) pattern identification for patients with mild cognitive impairment and early dementia. Patients and Methods: Twenty patients with mild cognitive impairment or mild dementia who planned to receive herbal medicine treatment were enrolled. Herbal formulae were prescrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…About 121 499 deaths were recorded from AD in 2019, the latest year for which data are available. Alzheimer's disease was officially listed as the sixth‐leading cause of death in the United States in 2019 and the seventh‐leading cause of death in 2020 and 2021, when COVID‐19 entered the ranks of the top 10 causes of death 3 . Regardless of the increasing prevalence of AD due to the world's aging population and related health problems, there are no effective strategies for the prevention and treatment of this disease 3 .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…About 121 499 deaths were recorded from AD in 2019, the latest year for which data are available. Alzheimer's disease was officially listed as the sixth‐leading cause of death in the United States in 2019 and the seventh‐leading cause of death in 2020 and 2021, when COVID‐19 entered the ranks of the top 10 causes of death 3 . Regardless of the increasing prevalence of AD due to the world's aging population and related health problems, there are no effective strategies for the prevention and treatment of this disease 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer's disease was officially listed as the sixth‐leading cause of death in the United States in 2019 and the seventh‐leading cause of death in 2020 and 2021, when COVID‐19 entered the ranks of the top 10 causes of death 3 . Regardless of the increasing prevalence of AD due to the world's aging population and related health problems, there are no effective strategies for the prevention and treatment of this disease 3 . Many studies have reported that higher levels of inflammatory cytokines such as interleukin‐1, interleukin −6 and tumor necrosis factor alpha (TNF‐α) in AD patients impair memory and learning performance 4 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations